Management outcome of epidural hematoma patients at Dessie Comprehensive Specialized Hospital: one-year prospective observational study - Tegegne, Belachew; Welelaw, Abebaw; Shumye, Mekuriaw Wuhib; Zeru, Leul Mekonnen (Frontiers in Surgery, 2025)
BackgroundEpidural hematoma is a life-threatening neurosurgical emergency that requires prompt intervention. In Ethiopia, epidural hematoma is linked to a high prevalence of morbidity and mortality. Despite the high burden of traumatic brain injuries in the region, there is a lack of local data on the management outcomes of epidural hematoma in Ethiopia.ObjectiveTo assess the management outcomes and associated factors of epidural hematoma at Dessie Comprehensive Specialized Hospital.MethodsAn institution-based prospective observational study was conducted among 46 patients at Dessie Comprehensive Specialized Hospital from January 2022 to January 2023. Data were extracted from morbidity/mortality reports, hospital records, and patient cards. Data were coded, entered into EpiData version 3.1, and analyzed using SPSS version 23. Chi-square test was used to identify factors associated with outcomes of epidural hematoma.ResultsAmong patients, 82.6% had good recovery, 10.9% severe disability, 2.2% persistent vegetative state, and 4.3% died. Injury mechanism (p = 0.001), headache history (p = 0.028), Glasgow Coma Scale score (p = 0.001), aspiration (p = 0.001), hypotension (p = 0.001), elevated intracranial pressure (p = 0.001), pupillary signs (p = 0.001), body weakness (p = 0.001), intracranial injury manifestation (p < 0.001), TBI severity (p = 0.001), computed tomography (CT) findings (p = 0.001), surgical procedure type (p = 0.003), and intensive care unit admission (p < 0.001) were significantly associated with the management outcomes of epidural hematoma.ConclusionThe majority of patients experienced favorable clinical outcomes. Outcomes of epidural hematoma management significantly associations with the mechanism of injury, presence of aspiration, prior headache history, Glasgow Coma Scale score, hypotension, elevated intracranial pressure, pupillary abnormalities, focal neurological deficits, and traumatic brain injury severity. Implementing context-specific policy interventions, enhanced safety protocols, and targeted public education initiatives could substantially reduce the incidence and impact of epidural hematomas in Ethiopia.